The Mediating Role of Public Service Managerial Capability and Adaptive Service Innovation in the Relationship between Citizen Orientation and Public Entrepreneurship toward Public Service Performance: Evidence from Creative Public Service Organizations in West Java, Indonesia - Asmala, Tuti; Kartawan, Kartawan; Sutisna, Deden; Pratminingsih, Sri Astuti (Universitas Padjadjaran, 2026)
This study examined how citizen orientation and public entrepreneurship affect public service performance through public service managerial capability and adaptive service innovation. Guided by the Resource-Based View, Dynamic Capabilities Theory, and Public Value Theory, it argued that citizen-centric and entrepreneurial orientations improved service outcomes when converted into managerial and innovative capacities. Using a quantitative explanatory design, data were collected from 334 managers and administrators in creative and cultural public service organizations across 27 cities and regencies in West Java, Indonesia. These included government cultural centers, vocational training institutions, creative economy agencies, and public-private partnerships. Structural Equation Modeling (SEM) with AMOS 24 tested the hypothesized relationships. The findings indicated that citizen orientation and public entrepreneurship significantly strengthen managerial capability and adaptive service innovation, which subsequently improve service performance. Both mediators exhibit significant partial and sequential mediation effects, confirming their joint role as dynamic mechanisms linking strategy to performance. The study expanded understanding of how creative public organizations can translate strategic orientations into improved service delivery and provides insights for policymakers and administrators to develop managerial capability and foster innovation in public service systems.